Influence of work competence and work environment on employee productivity: Study of pt lutvindo wijaya perkasa pekanbaru area - Nurmalinda; Okta Karneli; Mandataris (Enrichment : Journal of Management, 2023)
This research was conducted at PT. Lutvindo Wijaya Perkasa Pekanbaru. The purpose of this study was to determine the effect of work competence and work environment on work productivity at PT. Lutvindo Wijaya Perkasa Pekanbaru. Work competence and work environment as the Independent Variables (X) while work productivity is the Dependent Variable (Y). The problem in this study is the work productivity of employees who experience fluctuating numbers. The sample for this research was taken as many as 92 respondents from 120 populations which were calculated using the Slovin formula. The data obtained from the results of the questionnaires were distributed using a simple random sampling technique and then processed to then be tested statistically through SPSS 25 account= 13.749 > table 1.987 and sig 0.000 <0.05, then the work environment has a positive and significant effect on work productivity, where tcount= 13.461table 1.987 and sig 0.000 <0.05, as well as work competence and work environment on employee work productivity, where the value of fcaccount148,824) > ftable (3.10), and the significance value (0.000) <0.05.